How Did the World's Poorest Fare in the 1990s? - Chen, Shaohua; Ravallion, Martin (World Bank, Washington, DC, 2014)
Drawing on data from 265 national sample surveys spanning 83 countries, the authors find that there was a net decrease in the total incidence of consumption poverty between 1987 and 1998. But it was not enough to reduce the total number of poor people, by various definitions. The incidence of poverty fell in Asia and the Middle East and North Africa, changed little in Latin America and Sub-Saharan Africa, and rose in Eastern Europe and Central Asia. The two main proximate causes of the disappointing rate of poverty reduction: too little economic growth in many of the poorest countries, and persistent inequalities (in both income and other essential measures) that kept the poor from participating in the growth that did occur.